Integrasi Pendidikan Karakter dan Kewirausahaan di Sekolah Dasar: Sintesis Pendekatan Kurikuler-Ekstrakurikuler - Idham Kholid; Mulhat; Devi Yaniar Wi Hargina (CV. Insight Publisher, 2025)
In the context of preparing an outstanding generation for the 21st century, the integration of character education and entrepreneurship in elementary schools has become a crucial strategy, yet its implementation remains suboptimal and fragmented. This study aims to synthesize empirical evidence regarding the models, character values, and determining factors for the success of this integration. Through a Systematic Literature Review with qualitative meta-synthesis of 28 selected articles, the findings reveal that a hybrid approach—combining project-based learning (curricular) with programs such as market day (extracurricular)—proves most effective. This model not only instills instrumental values such as honesty and responsibility but also intrinsic character traits like resilience, with success heavily dependent on teachers' active agency and systemic school support. These findings highlight the need for a paradigm shift toward designing contextual and holistic learning approaches.